Depression during multiple sclerosis relapse: relation todisability and relapse severity - Selma Šabanagić-Hajrić; Enra Suljić; Gorana Sulejmanpašić-Arslanagić (Medicinski Glasnik, 2016)
Aim To examine the presence of depressive symptoms in patients with multiple sclerosis relapse and its relation to disability and relapse severity.